Chief executive scanning, environmental characteristics, and company performance: An empirical study - Daft, Richard L; Sormunen, Juhani; Parks, Don (Strategic Management Journal, 1988)
Abstract Chief executives in 50 manufacturing companies were interviewed about the perceived strategic uncertainty in six environmental sectors, and the frequency and mode of scanning used for each sector. The findings suggest that customer, economic and competitor sectors generated greater strategic uncertainty than technological, regulatory and sociocultural sectors. When sector uncertainty was high, executives reported greater frequency of scanning and greater use of personal information sources. Chief executives in high‐performing companies scanned more frequently and more broadly in response to strategic uncertainty than their counterparts in low‐performing companies.